The improvement of hazardous goods transportation technology - Batarliene, Nijole (Transport, 2004)
This article analyses the conception of the improvement of hazardous goods transportation technology as well as its theoretical principles. Basic organizational aspects of hazardous goods safe transportation are also represented. Effective and safe hazardous goods transportation is possible only using good informational supply. Process modelling and the creation of hazardous goods transportation informational system can improve each hazardous goods transportation technological process. This system should join its components on the whole and coordinate state institutions. The article studies the experience of foreign countries in the creation of informational systems. In the world developed countries various methods of safe dangerous goods transportation are used. This article analyses the types of informational technologies application problems, shows their schemes. It is noted that the solution of transport technology problems is based on the improvement of technological supply, the rational usage of informational modelling methodology of the whole transportation process. First Published Online: 27 Oct 2010